Exploring the potential antimalarial properties, safety profile, and phytochemical composition of Mesua ferrea Linn. - Atthaphon Konyanee; Prapaporn Chaniad; Arisara Phuwajaroanpong; Walaiporn Plirat; Parnpen Viriyavejakul; Abdi Wira Septama; Chuchard Punsawad (PLoS ONE)
The increased resistance of Plasmodium falciparum to artemisinin and its partner drugs poses a serious challenge to global malaria control and elimination programs. This study aimed to investigate the therapeutic potential of Mesua ferrea Linn., a medicinal plant, as a source for novel antimalarial compounds. In this study, we conducted in vitro assays to evaluate the antimalarial activity and cytotoxicity of crude extracts derived from M. ferrea L. leaves and branches. Subsequently, the most promising extracts were subjected to assessments of their antimalarial efficacy and acute oral toxicity tests in mouse models. Furthermore, selected crude extracts underwent gas chromatography-mass spectrometry (GC-MS) analysis to identify their phytochemical compositions. Our findings revealed that the ethanolic extract of M. ferrea L. branches (EMFB) exhibited high antimalarial activity, with an IC50 value of 4.54 μg/mL, closely followed by the ethanolic extract of M. ferrea L. leaves (EMFL), with an IC50 value of 6.76 μg/mL. Conversely, the aqueous extracts of M. ferrea L. branches (AMFB) and leaves (AMFL) exhibited weak and inactive activity, respectively. The selected extracts, EMFB and EMFL, demonstrated significant dose-dependent parasitemia suppression, reaching a maximum of 62.61% and 54.48% at 600 mg/kg body weight, respectively. Furthermore, the acute oral toxicity test indicated no observable toxicity at a dosage of 2,000 mg/kg body weight for both extracts. GC-MS analysis revealed abundant compounds in the EMFB, such as oleamide, cis-β-farnesene, alloaromadendrene, physcion, palmitic acid, 5-hydroxymethylfurfural, and 4H-pyran-4-one, 2,3-dihydro-3,5-dihydroxy-6-methyl-, while the EMFL contained friedelin, friedelinol, betulin, β-caryophyllene, oleamide, and 5-hydroxymethylfurfural. Notably, both extracts shared several phytochemical compounds, including 4H-pyran-4-one, 2,3-dihydro-3,5-dihydroxy-6-methyl-, 5-hydroxymethylfurfural, α-copaene, cyperene, β-caryophyllene, alloaromadendrene, palmitic acid, ethyl palmitate, and oleamide. Additionally, further study is needed to isolate and characterize these bioactive compounds from M. ferrea L. leaves and branches for their potential utilization as scaffolds in the development of novel antimalarial drugs.